Sero-survey of measles virus antibodies among symptomatic children attending Abuja Teaching Hospital, Nigeria - Adekola, Hafeez Aderinsayo; Abdullahi, Idris Nasir; Emeribe, Anthony Uchenna; Faruku, Nafiu; Uzairue, Leonard; Adeyemi Billyrose, Olusoji Matthew; Shuwa, Halima Ali (German Medical Science GMS Publishing House, 2021)
Background: Nigeria is one of the countries with a high prevalence of measles outbreak in children under 5 years old, despite a history of vaccination. This study aims to determine the prevalence of anti-measles virus IgM and IgG among children under 5 years attending the University of Abuja Teaching Hospital (UATH), Gwagwalada, FCT Abuja, Nigeria.Materials and methods: Whole blood was collected, centrifuged, and serum anti-IgM and anti-IgG against measles virus was analysed using ELISA. Sociodemographic variables and vaccination history of subjects were obtained by interview-based questionnaires.Results: The overall anti-Measles virus IgG and IgM seroprevalences were 29.2% and 14.6%, respectively. The prevalence of measles IgG was significantly associated with the parent's employment status (=11.67, p=0.008). However, the prevalence of measles virus IgM was significantly associated with children's age (=16.62, p=0.002), parents' employment status and children's vaccination status ( =7.72, p=0.02).Conclusion: A majority of study participants were not immunised against measles, and a significant number of participants had serological evidence of acute measles virus infection. There is a need for more concerted and massive measles vaccination of children.